Expert computer system for poultry farming - А.S. Sarzhan (Ukrainian Journal of Educational Studies and Information Technology, 2017)
The article deals with the problem of development of the modern expert system for chicken breeding. The author highlights the main features of the expert system: the simple and clear interface, the ability to make queries and get conclusions, choice of input data, the module of recommendations.